Nanostructuring of Mg-Based Hydrogen Storage Materials: Recent Advances for Promoting Key Applications - Ren, Li; Li, Yinghui; Zhang, Ning; Li, Zi; Lin, Xi; Zhu, Wen; Lu, Chong; Ding, Wenjiang; Zou, Jianxin (Nano-Micro Letters, 2023)
With the depletion of fossil fuels and global warming, there is an urgent demand to seek green, low-cost, and high-efficiency energy resources. Hydrogen has been considered as a potential candidate to replace fossil fuels, due to its high gravimetric energy density (142 MJ kg−1), high abundance (H2O), and environmental-friendliness. However, due to its low volume density, effective and safe hydrogen storage techniques are now becoming the bottleneck for the "hydrogen economy". Under such a circumstance, Mg-based hydrogen storage materials garnered tremendous interests due to their high hydrogen storage capacity ( 7.6 wt% for MgH2), low cost, and excellent reversibility. However, the high thermodynamic stability (ΔH = − 74.7 kJ mol−1 H2) and sluggish kinetics result in a relatively high desorption temperature (> 300 °C), which severely restricts widespread applications of MgH2. Nano-structuring has been proven to be an effective strategy that can simultaneously enhance the ab/de-sorption thermodynamic and kinetic properties of MgH2, possibly meeting the demand for rapid hydrogen desorption, economic viability, and effective thermal management in practical applications. Herein, the fundamental theories, recent advances, and practical applications of the nanostructured Mg-based hydrogen storage materials are discussed. The synthetic strategies are classified into four categories: free-standing nano-sized Mg/MgH2 through electrochemical/vapor-transport/ultrasonic methods, nanostructured Mg-based composites via mechanical milling methods, construction of core-shell nano-structured Mg-based composites by chemical reduction approaches, and multi-dimensional nano-sized Mg-based heterostructure by nanoconfinement strategy. Through applying these strategies, near room temperature ab/de-sorption (< 100 °C) with considerable high capacity (> 6 wt%) has been achieved in nano Mg/MgH2 systems. Some perspectives on the future research and development of nanostructured hydrogen storage materials are also provided. Highlights: 1 A comprehensive discussion of the recent advances in the nanostructure engineering of Mg-based hydrogen storage materials is presented. 2 The fundamental theories of hydrogen storage in nanostructured Mg-based hydrogen storage materials and their practical applications are reviewed. 3 The challenges and recommendations of current nanostructured hydrogen storage materials are pointed out.